Taking the bait: Developing a bait delivery system to target free‐ranging crocodiles and varanid lizards with a novel conservation strategy - Abhilasha Aiyer; Bunuba Rangers; Tina Bell; Richard Shine; Ruchira Somaweera; Miles Bruny; Georgia Ward‐Fear (Ecology and Evolution, 2022)
Abstract In tropical Australia, conditioned taste aversion (CTA) can buffer vulnerable native predators from the invasion of a toxic prey species (cane toads, Rhinella marina). Thus, we need to develop methods to deploy aversion‐inducing baits in the field, in ways that maximize uptake by vulnerable species (but not other taxa). We constructed and field‐tested baiting devices, in situ with wild animals. Apparatus were set next to waterbodies and baited concurrently at multiple locations (over water, water's edge, and on the bank). Baits were checked and replaced twice daily during the trial; remote cameras recorded visitation by native predators. Bait longevity was compared at sun‐exposed and shaded locations over 12 h. The strength required to remove baits from apparatus was measured in varanids and crocodiles. The device promoted high rates of bait uptake by freshwater crocodiles (47% baits consumed), varanid lizards (19% baits consumed), and non‐target taxa (34% baits consumed). Targeting specific predators can be achieved by manipulating bait location and time of deployment, as well as the force required to dislodge the bait. Crocodiles were best targeted with over‐water baits, whereas varanid lizards preferred baits located at the edges of waterbodies. When testing bait longevity in ambient conditions, during the daytime baits desiccated fully within 12 h, and faster in the sun than in the shade. Based on studies using captive animals, the “pulling force” strength of reptilian predators scaled with body size and was greater in crocodiles than in varanid lizards. We present the first conservation baiting protocol designed specifically for reptiles. Our results demonstrate the feasibility of widespread and taxon‐specific deployment of aversion‐inducing baits to buffer the impacts of invasive cane toads, and our methods are applicable (with modification) to other research and management programs globally.